2005
DOI: 10.1016/j.cell.2005.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Flt3+ Lympho-Myeloid Stem Cells Lacking Erythro-Megakaryocytic Potential

Abstract: All blood cell lineages derive from a common hematopoietic stem cell (HSC). The current model implicates that the first lineage commitment step of adult pluripotent HSCs results in a strict separation into common lymphoid and common myeloid precursors. We present evidence for a population of cells which, although sustaining a high proliferative and combined lympho-myeloid differentiation potential, have lost the ability to adopt erythroid and megakaryocyte lineage fates. Cells in the Lin-Sca-1+c-kit+ HSC compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

66
1,002
7
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,057 publications
(1,096 citation statements)
references
References 53 publications
66
1,002
7
6
Order By: Relevance
“…15 Whereas we had shown that most investigated genes affiliated with the Mk and E lineages are no longer expressed in LSKFlt3 hi cells, we did find that Mpl was still expressed in a fraction of LSKFlt3 hi cells, although at reduced levels and frequencies when compared with LSKCD34 Ϫ Flt3 Ϫ and LSKCD34 ϩ Flt3 Ϫ cells. 10,15 Of further note, the fraction of BM LSKFlt3 hi cells expressing Mpl coexpressed genes of the GM lineage but predominantly not of the lymphoid lineage, in contrast to LSKFlt3 hi cells negative for Mpl, which frequently coexpressed lymphoid and GM genes. 15 Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Whereas we had shown that most investigated genes affiliated with the Mk and E lineages are no longer expressed in LSKFlt3 hi cells, we did find that Mpl was still expressed in a fraction of LSKFlt3 hi cells, although at reduced levels and frequencies when compared with LSKCD34 Ϫ Flt3 Ϫ and LSKCD34 ϩ Flt3 Ϫ cells. 10,15 Of further note, the fraction of BM LSKFlt3 hi cells expressing Mpl coexpressed genes of the GM lineage but predominantly not of the lymphoid lineage, in contrast to LSKFlt3 hi cells negative for Mpl, which frequently coexpressed lymphoid and GM genes. 15 Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The strategy developed was based on 2 key findings common to our study and the Forsberg study. 10,11,18 First, that a small fraction (0.4%-1.2%) of LSKFlt3 hi cells are able to generate large MkE-enriched colonies in the spleen (spleen colony-forming unit [CFU-S] 10,11 and used as positive controls for in vitro assays and CFU-S assay, respectively. For detailed information, see Document S1 (available on the Blood website; see the Supplemental Materials link at the top of the online article).…”
Section: Introductionmentioning
confidence: 99%
“…G-CSF acts at the level of myeloid progenitors to induce their proliferation and differentiation. Its receptor, G-CSFR, is expressed throughout the myeloid lineage from early stem and progenitor cells to fully differentiated neutrophils 18,19 , and G-CSFR-STAT3 (signal transducer and activator of transcription 3) signaling governs neutrophil formation 20 . The transcription factor RAR-related orphan receptor γ1 (RORC1) is a recently identified regulator of myelopoiesis in tumor-bearing mice and its expression may be induced by G-CSF 21 .…”
Section: Granulopoiesismentioning
confidence: 99%
“…It is currently unclear at which differentiation step these molecules instruct phenotypic changes in neutrophils. For G-CSF, there is evidence that this cytokine can affect gene expression in stem or progenitor cells and fully differentiated cells as G-CSFR is expressed throughout neutrophil development 18,19 . These data suggest that neutrophil polarization is programmed early in the developmental process in the bone marrow, but when and where individual molecules shape neutrophil polarization needs further attention.…”
mentioning
confidence: 99%
“…The role of FLT3 differs between the mouse and the human system. In the mouse system, FLT3 expression is correlated with short-term reconstituting HSC (Lin-Sca-1+c-kit+FLT3+), whereas there is no evidence so far that it is also expressed in long-term repopulating (HSC) [8,9]. In human adult bone marrow (BM), FLT3 expression is restricted to CD34 + cells and a subset of dendritic precursors [10].…”
Section: Introductionmentioning
confidence: 99%